Apprenticeship-type schemes and structured work-based learning programmes : Germany - Hensen-Reifgens, Kristina Alice [Verfasser] (My University, 2014)
This article is the second one of a set of articles prepared within Cedefop's ReferNet network based on a common template. It provides an overview of the 'dual system' which forms the core element of existing apprenticeship programmes in Germany, looks at the specific features, the main strengths and weaknesses. (BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 1.3.1 Ausbildung im Dualen System; Berufsbildungspolitik; Duales System